Social aspects of tropical forest management - Colfer, C.J.P.; Center for International Forestry Research (2001)
This brief article begins with a summary of CIFOR's work on criteria and indicators for sustainable forest management (C&I). It then discusses how CIFOR programs combined to form the program called Local People, Devolution and Adaptive Collaborative Management of Forests". It briefly describes the research approach and the research design underway in 9 countries.